Kuttner is making a speech in front of the XI. International Brigade in Spain. Photo copied from Zentrales Staatsarchiv Potsdam collection - Schaul, Hans,
Kuttner is making a speech in front of the XI. International Brigade in Spain. Photo copied from Zentrales Staatsarchiv Potsdam collection.